1999
DOI: 10.1006/pmpp.1999.0232
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical composition related to fungal infection and induced resistance in carnation and radish investigated by pyrolysis mass spectrometry

Abstract: Pseudomonas fluorescens WCR 417r induces systemic resistance in radish roots challenged by Fusarium oxysporum f. sp. raphani and, incidentally, in carnation stems challenged by Fusarium oxysporum f. sp. dianthi. The induced systemic resistance is not associated with accumulation of pathogenesis-related proteins (PRs) or, at least in case of radish, with increased peroxidase activity. We tested whether the induced systemic resistance might be associated with changes in the host cell wall composition. Cell wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Meanwhile, the reduction in shoot dry weight might be related to increased rate of respiration and decompartementalization due to membrane degradation as suggested by Orcutt and Nilsen [24]. Furthermore, the present results showed that infection by B. fabae markedly decreased fresh and dry weights in roots of faba bean plants, and this may be related to the accumulation and action of phenolics produced from degradation of cell wall (lignin) mainly via depolymerization resulting from fungal elicitors [25].…”
Section: Discussionsupporting
confidence: 69%
“…Meanwhile, the reduction in shoot dry weight might be related to increased rate of respiration and decompartementalization due to membrane degradation as suggested by Orcutt and Nilsen [24]. Furthermore, the present results showed that infection by B. fabae markedly decreased fresh and dry weights in roots of faba bean plants, and this may be related to the accumulation and action of phenolics produced from degradation of cell wall (lignin) mainly via depolymerization resulting from fungal elicitors [25].…”
Section: Discussionsupporting
confidence: 69%
“…This hormonal imbalance in tomato seedling after Fusarium infection included the accumulation of ABA and reduction of IAA, GA3 and cytokinines (El-Khallal2007). In addition, the short root and shoot lengths in tomato seedlings infected with Fusarium oxysporum could be due to the production of some toxins by fungi and the accumulation of phenolic compounds produced from the cell wall degradation mainly lignin via depolymerization resulting from fungal elicitors (Steijl et al 1999, Hanaa et al 2011 The evolution of wilt disease incidence in tomato plants infected with Fusarium oxysporum f. sp. lycopersici was recorded at different time interval.…”
Section: Discussionmentioning
confidence: 99%
“…Meena et al (1999) got a substantial increase in phenyl alanine ammonia lyase activity in rice leaves sprayed with P. fluorescens Pf 1 strain one day after treatment, whereas maximum activity was observed 3 days after treatment. Steijl et al (1999) working with radish and carnation for control of F. oxysporum f. sp. raphani and F. oxysporum f. sp.…”
Section: Mechanism Of Actionmentioning
confidence: 99%